Method development and validation using liquid chromatography-mass spectrometry to quantify thyroid hormones rT3, T3, T4, and TSH - Sephesu, Liezel (University of the Witwatersrand, Johannesburg, 2024)
The thyroid gland produces three hormones namely: triiodothyronine (T3), thyroxine (T4) and Calcitonin. These play an important role in metabolism and development in the body. In addition to the thyroid hormones is reverse T3 (rT3), produced from the deiodination of T4. The production of these thyroid hormones is regulated by the Hypothalamus-Pituitary-Thyroid-Axis via thyrotropin releasing hormone (TRH) and thyroid stimulating hormone (TSH). Even with this regulation, thyroid hormone imbalances can occur in the body. Immunoassays (IA), the method used routinely for thyroid hormone measurement, can be affected by abnormal concentrations of albumin and other serum proteins leading to erroneous results. Furthermore, IAs have also been shown to be inaccurate at lower concentrations, causing possible misdiagnosis and health complications. Thus, alternative methods to measure thyroid hormone levels like liquid chromatography-tandem mass spectrometry (LC-MS/MS) are recommended as this method is not prone to interferences and has a better measuring range, particularly at the lower ranges. In the current study, an LC-MS/MS method for measuring free T3 (FT3), free T4 (FT4) and rT3, using commercially available standards was optimised and validated. The method was subsequently used to analyse 200 remnant samples previously measured by IA and the results from the two methods were compared. Samples with low thyroid hormone levels were prioritised when collecting remnant samples but the entire clinical measuring range was included. The correlation between the two methods was only seen at low concentrations (2-5 pmol/L for FT3 and 10-20 pmol/L for FT4). It was observed that more patients (40.5%) were diagnosed as being euthyroid using the IA method of measurement versus euthyroid sick syndrome diagnosis by LC-MS/MS (72.5%).
A research report submitted in fulfillment of the requirements for the Master of Science in Medicine, in the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; rT3; T3; T4; and TSH; liquid chromatography-mass; thyroid hormones; SDG-3: Good health and well-being